Efektivitas Penggunaan Media Flashcard dalam Pengajaran Kakikata to Yomikata III pada Mahasiswa UBINUS Semester Tiga Tahun Ajaran 2010/2011 - Timur Sri Astami (Lingua Cultura, 2010)
Article clarified the process of language learning, especially Japanese in a class environment, in which closely related to the teacher, material learning, and the learning media. In kakikata to yomikata subject (Writing and Reading III), students frequently got difficulties in reading or spelling kanji letters. To observe these difficulties, the researcher uses flashcard for developing the Japanese vocabularies in six weeks regularly in thirty minutes. The result indicates that around 64% of the respondents get significant developments. The positive impact on those successful respondents is their ability in remembering vocabularies as well as writes them in kanji letters.